An interdisciplinary perspective on environmental justice: integrating subjective beliefs and perceptions - Baasch, Stefanie (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
In this paper, environmental justice is considered from an interdisciplinary and integrative perspective that combines theories and studies in geography, environmental policy and planning with a justice psychology approach. This opens up an integrated view, which takes into account both societal and individual aspects of the perception and evaluation of environmental justice. In this sense, notions of environmental justice(s) are seen as the result of discursive processes, historical contexts and a social localization and standardization that is shaped by both cognitive evaluation processes and emotions. Additionally, environmental justice in participation processes is considered in the context of environmental and sustainability policy and its implementation, first summarising the points of criticism of participation processes and then discussing environmental justice as an aspect of participation practice. From this, some key points for a more justice-sensitive design of participation processes in the context of environmental and sustainability policies and programmes (e.g. adaptation to climate change, urban planning, energy system transformation) are derived. This interdisciplinary analysis shows that there is not ‘one’ environmental justice, but a multitude of ideas and evaluations based on different concepts and perceptions.